Whole-machine material migration studies in the TEXTOR tokamak with molybdenum. (August 2017) - Weckmann, A.; Petersson, P.; Kirschner, A.; Wienhold, P.; Brezinsek, S.; Kreter, A.; Pospieszczyk, A.; Rubel, M.
Highlights: Global Mo deposition measured on all main PFCs in TEXTOR. Mo concentration decreases exponentially. Decay lengths are in the order of 0.1–1 m. ERO simulations find similar decay lengths. Overall max. 22% of injected Mo is found locally and globally. Abstract: MoF6 injection from a localised source into plasma edge in the TEXTOR tokamak was the last experiment before the final shut-down of the TEXTOR machine. During decommissioning all plasma-facing components (PFCs) became available for surface studies. Detailed mapping of Mo deposition was performed in order to determine its migration on global scale. The concentration of Mo on PFC decays exponentially with distance from the source. The decay length is of the order of 0.1 m on the main PFC and 1 m on the receded components. Also the decay lengths modelled with the ERO code are between 0.15–1.3 m, depending on the anomalous cross-field diffusion coefficient. The inner bumper limiter is found to be the major repository for Mo. Material balance measurements show that only up to 22% of the injected Mo was detected on all the PFCs thus indicating that a large fraction of injected Mo may have been pumped out before being deposited.